2008
DOI: 10.1111/j.1442-2042.2008.02188.x
|View full text |Cite
|
Sign up to set email alerts
|

Discarding antimicrobial prophylaxis for transurethral resection of bladder tumor: A feasibility study

Abstract: Objectives:To evaluate the feasibility of discarding antimicrobial prophylaxis (AMP) for transurethral resection of bladder tumor (TURBT). Methods: One-hundred and sixty-two patients undergoing TURBT, with no risk factors for infectious complications were included in this prospective study between April 2006 and April 2008. Forty-four patients received single oral dose of 200 mg levofloxacin for AMP (LVFX group), and the remaining 118 received no AMP (no AMP group). Rates of postoperative infectious complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Finally, 42 original reports of trials were identified as meeting inclusion criteria for data extraction and were included in the final meta-analysis. [3142867]…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 42 original reports of trials were identified as meeting inclusion criteria for data extraction and were included in the final meta-analysis. [3142867]…”
Section: Resultsmentioning
confidence: 99%
“…In clean-contaminated urological surgeries, patients received AMP as follows: between January 2005 and September 2005: tazobactam sodium/piperacillin sodium (TAZ/PIPC) intravenously immediately before the surgery and for 3 days afterwards; between October 2005 and September 2006: TAZ/PIPC once immediately before the surgery; after October 2006: LVFX orally once immediately before the surgery [12,13]. In the transurethral resection of bladder tumors, patients received AMP as follows: between April and September 2006: LVFX orally once immediately before the surgery; after October 2006: no AMP was administered [23]. In contaminated urological surgeries using bowel segments, patients received cefmetazole on the operative day only, although prolonged operation and other morbidity risk factors may support the use of a prolonged regimen, which should be within three days according to the European Association of Urology guideline [21].…”
Section: Methodsmentioning
confidence: 99%
“…818,821,827,[830][831][832][833][834][835][836][837][838][839] Organisms such as S. aureus, coagulase-negative Staphylococcus species, and group A Streptococcus species are also a concern in procedures entering the skin with or without entering the urinary tract. 818,827,[830][831][832]838,840,841 There is also some concern with biofilm-forming bacteria (S. epidermidis and P. aeruginosa) in patients with prosthesis implantation. 842 Efficacy.…”
Section: Urologic Proceduresmentioning
confidence: 99%
“…6 Based on bioavailability, oral antimicrobial prophylaxis should be administered 1-2 hours before surgical incision or start of the procedure. 817,[819][820][821][822]824,826,836,838,840,848,851,855 Pediatric efficacy. Limited data on antimicrobial prophylaxis are available for pediatric patients undergoing urologic procedures.…”
Section: Urologic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation